Surface sterilization and shoot regeneration from node explant of Sabah snake grass (Clinacanthus nutans) using different concentration of Clorox, BAP and Kinetin - Mat Lazim, Nur Yusliza (2016)
A study was conducted to establish a suitable surface sterilization protocol to reduce microbial contamination and increasing node explant survival of Clinacanthus nutans. Three different surface sterilization treatment which are the use of Clorox at 20% for 10 and 15 minutes and 30% Clorox for 10 minutes were used in this study. It was observed that immersion of node explant in 20% Clorox for 10 minutes was the best treatment in reducing microbial contamination and increasing explant survival. Microbial contamination was reduced to 20% and explant survival increased to 80% by using this sterilization protocol. Another study was carried out to determine the best concentration of 6-benzylaminopurine (BAP) or Kinetin (Kin) in triggering shoot proliferation from node explant of Clinacanthus nutans. The node explants of Sabah Snake Grass that are cultured on full strength MS (Murashige and Skoog 1962) medium supplemented with 0.5 mg/l BAP showed the highest shoot proliferation with 2.85 shoot formed per explant.